Dissociation behaviors of coal-related model compounds in ionic liquids. (1st April 2019) - Lei, Zhiping; Dong, Lin; Kang, Shigang; Huang, Yaqin; Li, Zhanku; Yan, Jinchong; Shui, Hengfu; Wang, Zhicai; Ren, Shibiao; Pan, Chunxiu
Highlights: Dissociation of coal-related model compounds in ILs were studied. ILs have a significant effect on the thermal dissolution of the model compounds. ILs promote the dissociation interaction of bridge bonds in model compounds. B(SO3 H)mim]OTf has a significant effect on the cleavage of diphenylmethane and diphenyl ketone. [Bmim]Cl promotes the cleavage of the diphenyl ether. Abstract: Ionic liquids have demonstrated to be promising solvents for processing coal and biomass. Aiming to exploit ionic liquids (ILs) as media for degradation of coal, diphenylmethane (DPM), diphenyl ether (DPE), and diphenyl ketone (DPK) were used as coal-related compounds to study the degradation behaviors of weak-bond structures of coal in ionic liquids in this work. It was found that 1-sulfonic acid butyl-3-methylimidazolium 14 trifluoromethanesulfonate ([B(SO3H)mim]OTf), 1-ethyl-3-methylimidazolium acetate ([Emim]Ac) and 1-butyl-3-methyl-imidazolium chloride ([Bmim]Cl) have a significant effect on the thermal dissociation of the model compounds. [B(SO3 H)mim]OTf has a significant effect on the cleavage of DPM and DPK. [Bmim]Cl promotes the cleavage of the DPE. The dissociation effect of the model compound under the action of ionic liquid increases with the increase of reaction temperature. The interaction between the oxygen-containing functional groups in the model compound promotes the respective thermal dissociation of the model compounds. Ionic liquids promote the dissociation interaction of bridge bonds in model compounds. Under the action of ionic liquids, the carbonyl bond promotes the cleavage of the methylene and ether bond cleavage, and the ether bond promotes the methylene bond cleavage.